Cu / Mn co-doped CoO / FeO catalyst and preparation method and application thereof

Through Cu/Mn co-doped CoO/FeO catalyst, the problems of low catalytic efficiency and insufficient stability of CoO nanomaterials are solved, and the PCB in organic wastewater is efficiently and stably treated, and the preparation process is simple.

CN119455976BActive Publication Date: 2025-04-04WEIFANG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510044780.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing CoO nanomaterials have problems with low catalytic efficiency, insufficient stability and complex preparation processes, making it difficult to effectively deal with difficult-to-degrade organic pollutants such as PCBs in organic wastewater.

Method used

CoO nanoparticles were grown on the FeO film by electrodeposition method using Cu/Mn co-doped CoO/FeO catalyst, and Cu2+ and Mn2+ ions were added to the electrolyte to form the CuxMny@Co1−x-yO/FeO catalyst.

Benefits of technology

The specific surface area and catalytic activity of the catalyst are improved, the adsorption and degradation efficiency of PCBs is enhanced, the service life of the catalyst is extended, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455976B_ABST
    Figure CN119455976B_ABST
Patent Text Reader

Abstract

The present invention discloses a Cu / Mn co-doped CoO / FeO catalyst and its preparation method and application, belonging to the field of photoelectrocatalysis technology. The preparation method comprises the following steps: 1) cleaning the iron mesh carrier; 2) preparing the FeO film: using the electrodeposition method, the electrolyte is FeSO 4 solution and a mixed solution of lactic acid to prepare Fe(OH) 2 Thin film, Fe(OH) 2 The film is calcined to obtain an FeO film; 3) CoO nanoparticles are grown on the surface of the FeO film: the electrolyte is a mixed solution of a cobalt nitrate solution and a hexamethylenetetramine HMTA solution, and CoO nanocrystals are synthesized by electrodeposition on the FeO film; 4) The catalyst is obtained by adding a copper chloride solution and a manganese nitrate solution to the electrolyte solution for co-doping. The catalyst of the present invention has a large specific surface area and many oxygen vacancies, which can improve the lattice stability and chemical stability of the catalyst and extend the service life of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrocatalysis, and specifically relates to a Cu / Mn co-doped CoO / FeO catalyst and a preparation method and application thereof. Background Art

[0002] In the field of catalyst research and development, especially for catalysts for organic wastewater treatment, traditional catalyst materials, such as those prepared by physical mixing and sol-gel methods, have long faced problems such as low catalytic efficiency, insufficient stability or complicated preparation processes. These problems are particularly prominent when treating highly stable and difficult to biodegrade organic pollutants such as polychlorinated biphenyls. Therefore, it is particularly urgent to develop a catalyst that is both efficient and stable and has a simple preparation process.

[0003] Although traditional preparation methods can generate catalytically active materials to a certain extent, their defects are also significant. For example, the uneven distribution of catalyst particles makes it difficult to maximize the utilization of reactive sites, and the small specific surface area limits the contact area of ​​the catalytic reaction, which in turn affects the catalytic efficiency. In addition, harsh preparation conditions such as high temperature and high pressure not only greatly increase production costs, but may also cause environmental pollution problems, limiting the promotion of these catalysts in practical applications.

[0004] In recent years, CoO nanomaterials have attracted extensive attention in the field of catalysts due to their suitable energy band structure, low cost, abundant resources, good chemical stability and low secondary pollution risk. However, CoO nanomaterials also face challenges in practical applications, mainly manifested in low light energy utilization, poor charge transfer ability and insufficient surface catalytic active sites, which seriously restrict the improvement of their catalytic efficiency. Therefore, it is necessary to overcome the limitations of CoO nanomaterials and prepare a catalyst with high catalytic activity to better suit the degradation of pollutants in organic wastewater. Summary of the invention

[0005] The present invention provides a Cu / Mn co-doped CoO / FeO catalyst and a preparation method and application thereof, which solve the problems of low catalytic efficiency, insufficient stability and complex preparation process of existing CoO nanomaterials, and provide an efficient, stable and easy-to-prepare catalyst solution for the treatment of polychlorinated biphenyls (PCBs) difficult-to-degrade organic pollutants in organic wastewater.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, a method for preparing a Cu / Mn co-doped CoO / FeO catalyst is disclosed, comprising the following steps:

[0008] 1) Cleaning of iron mesh carrier: Use dilute acid to remove the oxide layer on the surface of the iron mesh, rinse the iron mesh, and dry it;

[0009] 2) Preparation of FeO film: Electrodeposition method was used, with Ag / AgCl as reference electrode, platinum sheet as counter electrode, iron mesh as working electrode, and FeSO as electrolyte. 4 The mixed solution of solution and lactic acid, adjust the pH value of the electrolyte to 10-12, at a temperature of 60-80 ° C, the deposition voltage is - (0.6-0.8) V SAE Under the condition of precipitation for 5-8min, Fe(OH) 2 Thin film, Fe(OH) 2 The film is calcined at 200-400° C. for 1-2 hours under an argon atmosphere to obtain a FeO film with a thickness of 1 nm to 10 nm.

[0010] 3) Growth of CoO nanoparticles on the surface of FeO film: The FeO film prepared in step 2) is placed in a mixed solution of cobalt nitrate solution and hexamethylenetetramine HMTA solution as electrolyte, the pH of the solution is adjusted to 8-10, the temperature is 70-90°C, and the deposition voltage is -(1.0-1.2)V SAE CoO nanocrystals were synthesized on the FeO film after deposition for 10-20 min. The particle size of the nanocrystals was 50-100 nm.

[0011] 4) During the deposition of CoO nanoparticles, copper chloride solution and manganese nitrate solution were added to the electrolyte to obtain Mn / Cu ion co-doped CoO / FeO catalyst Cu x Mn y @Co 1−x-y O / FeO, wherein 0<x<0.1, 0<y<0.1.

[0012] Preferably, the dilute acid in step 1) is dilute hydrochloric acid or dilute sulfuric acid.

[0013] Preferably, in step 2) the electrolyte contains FeSO 4 The concentration of the solution is 0.3-0.5 mol / L, and the concentration of lactic acid is 2-4 mol / L.

[0014] Preferably, in step 3), the concentration of the cobalt nitrate solution is 1.4-2 mol / L, and the concentration of the hexamethylenetetramine HMTA solution is 0.08-0.12 mol / L.

[0015] Preferably, in steps 2) and 3), the pH is adjusted using ammonia water, sodium hydroxide or potassium hydroxide solution with a mass concentration of 25%.

[0016] Preferably, in step 3), Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter electrode, and an iron mesh containing a FeO film is used as a working electrode.

[0017] Preferably, the concentration of the copper chloride solution in step 4) is 0.1-0.3 mol / L, the concentration of the manganese nitrate solution is 0.2-0.3 mol / L, and the addition of Cu in step 4) 2+ and Mn 2+ The molar ratio is (2:1)-(1:1.3).

[0018] In the second aspect, the Mn / Cu ion co-doped CoO / FeO catalyst Cu prepared by the preparation method is disclosed. x Mn y @Co 1−x-y O / FeO, wherein 0<x<0.1, 0<y<0.1.

[0019] In a third aspect, the use of the Cu / Mn co-doped CoO / FeO catalyst in catalytic degradation of polychlorinated biphenyls in organic wastewater is disclosed, comprising the following steps:

[0020] a) The Mn / Cu ion co-doped CoO / FeO catalyst is placed in a quartz glass tube of a liquid film photoreactor, and the set temperature of the liquid film photoreactor is 20-30°C and the pressure is 0.1-0.3MPa;

[0021] b) adding the organic wastewater to be treated into the quartz tube, placing the catalyst in the organic wastewater, sealing the quartz tube, and introducing argon into the liquid film photoreactor under dark conditions at a flow rate of 90-110 mL / min for 20-40 min, and exhausting the gas in the reactor;

[0022] c) Under the irradiation of a xenon lamp with an irradiation power of 300-400W, the concentration of polychlorinated biphenyls before and after the reaction is measured after 5-10 hours of reaction.

[0023] The in-situ doping of Cu and Mn ions in CoO / FeO nanomaterials not only changes the crystal structure and electron distribution of the materials, but also introduces new surface defects. These surface defects, as active centers, play a vital role in the catalytic process. They can capture electrons from the catalyst and transfer these electrons to the adsorbed PCB molecules, thereby accelerating the catalytic reaction. The introduction of bimetallic ions also promotes the formation of more mesopores. The presence of mesopores not only increases the specific surface area of ​​the catalyst and provides abundant reaction sites, but also enhances the adsorption capacity of the catalyst for PCB molecules. This enhancement of adsorption capacity helps to gather more reactant molecules on the catalyst surface, thereby promoting their contact and reaction with the active centers.

[0024] In Cu x Mn y @Co 1−x-yIn the O / FeO catalyst, the abundant oxygen vacancies significantly reduce the band gap width of CoO / FeO, allowing the material to absorb light better. This change not only improves the light absorption capacity of the material, but also promotes the generation of photogenerated electrons and holes, providing more energy sources for the catalytic reaction; in addition to reducing the band gap, the oxygen vacancies themselves can also serve as active sites for the catalytic reaction. They can adsorb and activate polychlorinated biphenyl molecules, reduce the activation energy of the reaction, and thus accelerate the process of the catalytic reaction.

[0025] In Cu x Mn y @Co 1−x-y In the O / FeO catalyst, since CoO and FeO have different conductivity types (p-type and n-type, respectively), a pn heterojunction is formed between them. This heterojunction structure promotes the effective transfer and separation of photogenerated carriers in the catalytic process. Under light conditions, CoO and FeO generate photogenerated electrons and holes, respectively. Due to the presence of the pn heterojunction, these photogenerated electrons and holes can be directed and separated under the action of the electric field. Specifically, the photogenerated electrons are transferred from n-type FeO to p-type CoO, while the photogenerated holes are transferred in the opposite direction. This transfer and separation process effectively inhibits the recombination of photogenerated carriers and improves their utilization and catalytic activity.

[0026] The surface defects caused by in-situ doping of Cu and Mn ions act as active centers to capture electrons from the catalyst and transfer them to the adsorbed PCB molecules. With the introduction of bimetallic ions, the formation of more mesopores expands the specific surface area of ​​the catalyst, generates abundant reaction sites on the catalyst surface, and enhances the adsorption and activation of PCB molecules. The presence of oxygen vacancies reduces the band gap and enhances the absorption of visible light. In addition, the pn heterostructure promotes the efficient transfer and separation of photogenerated carriers.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. CoO / FeO catalyst Cu co-doped with Mn / Cu ions prepared by the present invention x Mn y @Co 1−x-y Compared with traditional CoO nanomaterials, O / FeO has a larger specific surface area and more oxygen vacancies. The doping of Cu and Mn can also improve the lattice stability and chemical stability of the catalyst, making it less likely to be deactivated or poisoned during the catalytic process, thereby extending the service life of the catalyst.

[0029] 2. The Mn / Cu ion co-doped CoO / FeO catalyst prepared by the present invention effectively regulates the structure and performance of the CoO / FeO catalyst through the co-doping of Cu and Mn, increases the catalytic active sites, and thus improves the catalytic degradation efficiency of the catalyst for organic pollutants such as polychlorinated biphenyls.

[0030] 3. The present invention adopts the electrodeposition method to prepare the catalyst, which has the advantages of simple process, convenient operation, easy control, etc. compared with the traditional sol-gel method, physical mixing method, etc. At the same time, the electrodeposition method can also realize the uniform deposition of the catalyst on the surface of the carrier, thereby increasing the specific surface area and catalytic activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a morphology picture of the Cu / Mn co-doped CoO / FeO catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0033] Example 1

[0034] The Cu / Mn co-doped CoO / FeO catalyst consists of an iron mesh and active components CuO, MnO attached to the iron mesh. 2 , CoO and FeO, and the loading amount of active ingredients is 5% of the mass of the iron mesh.

[0035] The method for preparing the Cu / Mn co-doped CoO / FeO catalyst comprises the following steps:

[0036] 1) Cleaning of the iron mesh carrier: Soak it in 0.1 mol / L dilute hydrochloric acid for 3 hours to remove the oxide layer on the surface of the iron mesh, rinse the iron mesh with deionized water, and dry it at 60℃ for 8 hours;

[0037] 2) Preparation of FeO film: Electrodeposition method was used, with Ag / AgCl as reference electrode, platinum sheet as counter electrode, iron mesh as working electrode, and electrolyte of 0.3 mol / L FeSO 4 The solution and 2 mol / L lactic acid were mixed in a volume ratio of 1:1 to obtain a mixed solution. The pH value of the electrolyte was adjusted to 10 with 25% ammonia water. The temperature was 60°C and the deposition voltage was -0.6V. SAE Under the condition of 5min deposition, Fe(OH) 2 Thin film, Fe(OH) 2The film was calcined at 200°C for 1 h under an argon atmosphere to obtain a FeO film with a thickness of 1 nm.

[0038] 3) Growth of CoO nanoparticles on the surface of FeO film: The FeO film prepared in step 2) was placed in a mixed solution of 2 mol / L cobalt nitrate solution and 0.08 mol / L hexamethylenetetramine HMTA solution in a volume ratio of 1:1. 0.1 mol / L copper chloride solution was added to the electrolyte, and the volume was 30% of the volume of the cobalt nitrate solution. Ag / AgCl was used as a reference electrode, a platinum sheet was used as a counter electrode, and an iron mesh containing a FeO film was used as a working electrode. The solution pH was adjusted to 8 with 25% ammonia water, and the deposition voltage was -1.0 V at a temperature of 70°C. SAE CoO nanocrystals doped with Cu were synthesized on the FeO film after deposition for 5 min. The film was taken out and dried for 4 h, and then placed in a tube furnace in an argon environment and calcined at 500 °C for 1 h. A 0.2 mol / L manganese nitrate solution was added to the electrolyte, and Cu 2+ and Mn 2+ The molar ratio of Mn / Cu ions was 2:1. After deposition for 5 minutes, the catalyst was taken out and dried for 4 hours, and then calcined at 400°C in a tube furnace in an argon environment for 2 hours to obtain the Mn / Cu ion co-doped CoO / FeO catalyst Cu 0.03 Mn 0.02 @Co 0.95 The particle size of O / FeO and CoO nanocrystals is 50 nm.

[0039] The morphology of the Cu / Mn co-doped CoO / FeO catalyst prepared in Example 1 is shown in FIG. Figure 1 shown.

[0040] The use of the Cu / Mn co-doped CoO / FeO catalyst in catalytic degradation of polychlorinated biphenyls in organic wastewater comprises the following steps:

[0041] a) The Mn / Cu ion co-doped CoO / FeO catalyst was placed in a quartz glass tube of a liquid film photoreactor, and the set temperature of the liquid film photoreactor was 20°C and the pressure was 0.1 MPa;

[0042] b) Add the organic wastewater to be treated into the quartz tube, place the catalyst in the organic wastewater, seal the quartz tube, and introduce argon into the liquid film photoreactor under dark conditions at a flow rate of 90 mL / min for 20 min, and exhaust the gas in the reactor;

[0043] c) Under the irradiation of a xenon lamp with an irradiation power of 300 W, the concentrations of PCBs before and after the reaction were measured after 5 hours of reaction.

[0044] Example 2

[0045] The Cu / Mn co-doped CoO / FeO catalyst consists of an iron mesh and active components CuO, MnO attached to the iron mesh. 2 , CoO and FeO, and the loading amount of active ingredients is 8% of the mass of the iron mesh.

[0046] The method for preparing the Cu / Mn co-doped CoO / FeO catalyst comprises the following steps:

[0047] 1) Cleaning of the iron mesh carrier: Soak in 0.2 mol / L dilute hydrochloric acid for 2 hours to remove the oxide layer on the surface of the iron mesh, rinse the iron mesh with deionized water, and dry at 60°C for 8 hours;

[0048] 2) Preparation of FeO film: Electrodeposition method was used, with Ag / AgCl as reference electrode, platinum sheet as counter electrode, iron mesh as working electrode, and electrolyte of 0.4 mol / L FeSO 4 The solution was mixed with 3 mol / L lactic acid in a volume ratio of 1:1, and the pH value of the electrolyte was adjusted to 11 with a 0.1 mol / L sodium hydroxide solution. The deposition voltage was -0.7 V at a temperature of 70 °C. SAE Under the condition of 6min deposition, Fe(OH) 2 Thin film, Fe(OH) 2 The film was calcined at 300°C for 1.5 h under an argon atmosphere to obtain a FeO film with a thickness of 5 nm.

[0049] 3) Growth of CoO nanoparticles on the surface of FeO film: The FeO film prepared in step 2) was placed in a mixed solution of 1.4 mol / L cobalt nitrate solution and 0.1 mol / L hexamethylenetetramine HMTA solution in a volume ratio of 1:1. 0.2 mol / L cupric chloride solution was added to the electrolyte, and the volume was 30% of the volume of the cobalt nitrate solution. Ag / AgCl was used as a reference electrode, a platinum sheet was used as a counter electrode, and an iron mesh containing the FeO film was used as a working electrode. The solution pH was adjusted to 10 with a sodium hydroxide solution, and the deposition voltage was -1.1 V at a temperature of 80°C. SAE CoO nanocrystals doped with Cu were synthesized on the FeO film after deposition for 8 min. The film was taken out and dried for 4 h, and then placed in a tube furnace in an argon environment and calcined at 500 °C for 1 h. A 0.25 mol / L manganese nitrate solution was added to the electrolyte, and Cu 2+ and Mn 2+ The molar ratio of Mn / Cu ions was 1:1.3. After deposition for 8 minutes, the catalyst was taken out and dried for 4 hours, and then calcined at 400 °C in a tube furnace in an argon environment for 2 hours to obtain the Mn / Cu ion co-doped CoO / FeO catalyst Cu 0.04 Mn 0.05 @Co0.91 O / FeO, the particle size of CoO nanocrystals is 80nm.

[0050] The use of the Cu / Mn co-doped CoO / FeO catalyst in catalytic degradation of polychlorinated biphenyls in organic wastewater comprises the following steps:

[0051] a) The Mn / Cu ion co-doped CoO / FeO catalyst was placed in a quartz glass tube of a liquid film photoreactor, and the set temperature of the liquid film photoreactor was 25°C and the pressure was 0.2MPa;

[0052] b) Add the organic wastewater to be treated into the quartz tube, place the catalyst in the organic wastewater, seal the quartz tube, and introduce argon into the liquid film photoreactor under dark conditions at a flow rate of 100 mL / min for 30 min, and exhaust the gas in the reactor;

[0053] c) Under the irradiation of a xenon lamp with an irradiation power of 350W, the concentrations of PCBs before and after the reaction were measured after 7 hours of reaction.

[0054] Example 3

[0055] The Cu / Mn co-doped CoO / FeO catalyst consists of an iron mesh and active components CuO, MnO attached to the iron mesh. 2 , CoO and FeO, and the loading amount of active ingredients is 10% of the mass of the iron mesh.

[0056] The method for preparing the Cu / Mn co-doped CoO / FeO catalyst comprises the following steps:

[0057] 1) Cleaning of the iron mesh carrier: Soak in 0.1 mol / L dilute hydrochloric acid for 4 hours to remove the oxide layer on the surface of the iron mesh, rinse the iron mesh with deionized water, and dry at 70°C for 6 hours;

[0058] 2) Preparation of FeO film: Electrodeposition method was used, with Ag / AgCl as reference electrode, platinum sheet as counter electrode, iron mesh as working electrode, and electrolyte of 0.5 mol / L FeSO 4 The solution and 4 mol / L lactic acid were mixed in a volume ratio of 1:1 to obtain a mixed solution. The pH value of the electrolyte was adjusted to 12 with a 0.1 mol / L potassium hydroxide solution. The deposition voltage was -0.8 V at a temperature of 80 °C. SAE Under the condition of 8min deposition, Fe(OH) 2 Thin film, Fe(OH) 2 The film was calcined at 400°C for 2h under an argon atmosphere to obtain a FeO film with a thickness of 10nm.

[0059] 3) Growth of CoO nanoparticles on the surface of FeO film: The FeO film prepared in step 2) was placed in a mixed solution of 1.5 mol / L cobalt nitrate solution and 0.12 mol / L hexamethylenetetramine HMTA solution in a volume ratio of 1:1. 0.3 mol / L cupric chloride solution was added to the electrolyte, and the volume was 30% of the volume of the cobalt nitrate solution. Ag / AgCl was used as a reference electrode, a platinum sheet was used as a counter electrode, and an iron mesh containing the FeO film was used as a working electrode. The solution pH was adjusted to 9 with potassium hydroxide solution, and the deposition voltage was -1.2 V at a temperature of 90°C. SAE The Cu-doped CoO nanocrystals were synthesized on the FeO film after deposition for 10 min. The Cu-doped CoO nanocrystals were taken out and dried for 4 h. The Cu-doped CoO nanocrystals were calcined for 1 h at 500 °C in an argon environment. A 0.3 mol / L manganese nitrate solution was added to the electrolyte. 2+ and Mn 2+ The molar ratio of Mn / Cu ions was 1:1.1. After 10 min of deposition, the catalyst was taken out and dried for 4 h, and then calcined at 400 °C in a tube furnace in an argon environment for 2 h to obtain the Mn / Cu ion co-doped CoO / FeO catalyst Cu 0.05 Mn 0.05 @Co 0.9 The particle size of O / FeO and CoO nanocrystals is 100 nm.

[0060] The use of the Cu / Mn co-doped CoO / FeO catalyst in catalytic degradation of polychlorinated biphenyls in organic wastewater comprises the following steps:

[0061] a) The Mn / Cu ion co-doped CoO / FeO catalyst was placed in a quartz glass tube of a liquid film photoreactor, and the set temperature of the liquid film photoreactor was 30°C and the pressure was 0.3MPa;

[0062] b) Add the organic wastewater to be treated into the quartz tube, place the catalyst in the organic wastewater, seal the quartz tube, and introduce argon into the liquid film photoreactor under dark conditions at a flow rate of 110 mL / min for 40 min, and exhaust the gas in the reactor;

[0063] c) Under the irradiation of a xenon lamp with an irradiation power of 400 W, the concentrations of PCBs before and after the reaction were measured after 10 hours of reaction.

[0064] Comparative Example 1

[0065] The difference from Example 1 is that in step 4) of this comparative example, no cupric chloride solution is added, and the remaining preparation methods and steps are the same as those of Example 1.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that in step 4) of this comparative example, no manganese nitrate solution is added, and the remaining preparation methods and steps are the same as those of Example 1.

[0068] Comparative Example 3

[0069] The difference from Example 1 is that in step 2), the FeO film is prepared by electrodeposition, Ag / AgCl is used as the reference electrode, platinum sheet is used as the counter electrode, iron mesh is used as the working electrode, and the electrolyte is 0.1 mol / L FeSO 4 The solution and 2 mol / L lactic acid were mixed in a volume ratio of 1:1 to obtain a mixed solution. The pH value of the electrolyte was adjusted to 10 with 25% ammonia water. The temperature was 60°C and the deposition voltage was -0.6V. SAE Under the condition of 5min deposition, Fe(OH) 2 Thin film, Fe(OH) 2 The film was calcined at 200°C for 1 h under an argon atmosphere to obtain a FeO film with a thickness of 0.8 nm.

[0070] Comparative Example 4

[0071] The difference from Example 1 is that 3) CoO nanoparticles are grown on the surface of the FeO film: the FeO film prepared in step 2) is placed in a mixed solution of 2 mol / L cobalt nitrate solution and 0.08 mol / L hexamethylenetetramine HMTA solution in a volume ratio of 1:1, 0.1 mol / L cupric chloride solution is added to the electrolyte, and the volume added is 30% of the volume of the cobalt nitrate solution, Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter electrode, and an iron mesh containing the FeO film is used as a working electrode; 25% ammonia water is used to adjust the solution pH to 8, and the temperature is 70°C and the deposition voltage is -1.0V. SAE CoO nanocrystals doped with Cu were synthesized on the FeO film after deposition for 16 min. The film was taken out and dried for 4 h, and then placed in a tube furnace in an argon environment and calcined at 500 °C for 1 h. A 0.2 mol / L manganese nitrate solution was added to the electrolyte, and Cu 2+ and Mn 2+ The molar ratio of Mn / Cu ions was 2:1. After deposition for 5 minutes, the catalyst was taken out and dried for 4 hours, and then calcined at 400°C in a tube furnace in an argon environment for 2 hours to obtain the Mn / Cu ion co-doped CoO / FeO catalyst Cu 0.03 Mn 0.02 @Co 0.95 The particle size of O / FeO and CoO nanocrystals is 200 nm.

[0072] Comparative Example 5

[0073] The difference from Example 1 is that 3) CoO nanoparticles are grown on the surface of the FeO film: the FeO film prepared in step 2) is placed in a mixed solution of 2 mol / L cobalt nitrate solution and 0.08 mol / L hexamethylenetetramine HMTA solution in a volume ratio of 1:1, 0.1 mol / L copper chloride solution is added to the electrolyte, the volume of which is 30% of the volume of the cobalt nitrate solution, 0.2 mol / L manganese nitrate solution is added to the electrolyte, and Cu is added. 2+ and Mn 2+ The molar ratio was 2:1, Ag / AgCl was used as the reference electrode, platinum sheet was used as the counter electrode, and the iron mesh containing FeO film was used as the working electrode; 25% ammonia water was used to adjust the solution pH to 8, the temperature was 70°C, and the deposition voltage was -1.0V SAE The catalyst was deposited for 10 min under the conditions of argon gas and then taken out and dried for 4 h. The catalyst was then placed in a tube furnace and calcined at 500 °C for 1 h to obtain the Mn / Cu ion co-doped CoO / FeO catalyst Cu. 0.03 Mn 0.02 @Co 0.95 The particle size of O / FeO and CoO nanocrystals is 50 nm.

[0074] The catalysts prepared in the above examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] It can be seen from the above table that the catalyst prepared by the present invention has a large average bulk density, a large average specific surface area, a large average pore volume and a large average pore diameter, which are all better than those of the comparative example.

[0078] The catalysts prepared in the above examples and comparative examples were used to degrade polychlorinated biphenyls in organic wastewater. The test results are shown in Table 2.

[0079] Table 2 Test results of polychlorinated biphenyls in organic wastewater degraded by the examples and comparative examples

[0080]

[0081] Degradation rate calculation formula:

[0082] ;

[0083] η is the degradation efficiency of PCBs, C 0 and C t are the initial concentration of PCBs and the concentration at time t, respectively.

[0084] As can be seen from Table 1, in Comparative Example 1, no copper chloride solution was added, and Cu was missing from the active ingredient. x Mn y @Co 1−x-y Cu plays multiple roles in O / FeO catalysts, including introducing surface defects, promoting mesopore formation, and enhancing light absorption. Therefore, the lack of Cu will lead to a decrease in the specific surface area of ​​the catalyst, a decrease in the number of active sites, and a decrease in light absorption capacity, thus affecting the catalytic performance.

[0085] In Comparative Example 2, no manganese nitrate solution was added, and Mn was missing from the active ingredients. The doping of Mn ions also has an important influence on the performance of the catalyst, and it can work together with Cu ions to further regulate the structure and performance of the catalyst. The lack of Mn will lead to a decrease in the lattice stability of the catalyst, and will also affect the formation of mesopores and the effective transfer of photogenerated carriers, thereby reducing the catalytic activity.

[0086] In Comparative Example 3, the thickness of the FeO film is too thin, and the FeO content generated is too little. As an important component of the catalyst, the reduction of FeO content will lead to a decrease in the overall performance of the catalyst. In particular, the pn heterojunction formed between FeO and CoO is crucial for the effective transfer and separation of photogenerated carriers. Therefore, insufficient FeO content will seriously affect the photocatalytic performance of the catalyst.

[0087] In Comparative Example 4, the particle size of the CoO nanocrystals is too large. Too large a particle size will reduce the specific surface area and the number of active sites, which will affect the recombination of photogenerated carriers and further affect the catalytic performance.

[0088] In Comparative Example 5, the timing of adding the copper chloride solution and manganese nitrate was changed. The change in the timing of addition would affect the distribution and doping degree of Cu and Mn ions in the CoO / FeO catalyst, thereby further affecting the structure and performance of the catalyst. For example, if the timing of addition is inappropriate, it may result in that Cu and Mn ions cannot be effectively doped into the catalyst, or the doping is uneven, thereby affecting the catalytic activity of the catalyst.

[0089] The catalyst prepared in Example 1 was subjected to a cyclic performance test. The specific catalytic method was the same as that in Example 1. After one catalytic reaction, the activity of the catalyst needed to be restored. Specifically, the catalyst after the reaction was first washed with deionized water, dried for 11 hours, and then placed in a tubular furnace for calcination for 8 hours at a heating temperature of 650°C. The degradation rate after 10 cycles is shown in Table 3.

[0090] Table 3 Degradation rate of cycle performance test

[0091]

Claims

1. A method for preparing a Cu / Mn co-doped CoO / FeO catalyst, characterized in that: The following steps are involved: 1) Cleaning of iron mesh carrier: Use dilute acid to remove the oxide layer on the surface of the iron mesh, rinse the iron mesh, and dry it; 2) Preparation of FeO film: Electrodeposition method was used, with Ag / AgCl as reference electrode, platinum sheet as counter electrode, iron mesh as working electrode, electrolyte was a mixed solution of FeSO4 solution and lactic acid, pH value of electrolyte was adjusted to 10-12, temperature was 60-80℃, deposition voltage was -(0.6-0.8)V SAE The Fe(OH)2 film was prepared by deposition for 5-8 minutes. The Fe(OH)2 film was calcined at 200-400°C for 1-2 hours in an argon atmosphere to obtain a FeO film with a thickness of 1nm-10nm. 3) Growth of CoO nanoparticles on the surface of FeO film: The FeO film prepared in step 2) is placed in a mixed solution of cobalt nitrate solution and hexamethylenetetramine solution as electrolyte, the pH of the solution is adjusted to 8-10, the temperature is 70-90°C, and the deposition voltage is -(1.0-1.2)V SAE CoO nanocrystals were synthesized on the FeO film after deposition for 10-20 min, and the particle size of the nanocrystals was 50-100 nm. 4) During the deposition of CoO nanoparticles, copper chloride solution and manganese nitrate solution were added to the electrolyte to obtain Mn / Cu ion co-doped CoO / FeO catalyst Cu x Mn y @Co 1-x-y O / FeO, wherein 0<x<0.1, 0<y<0.

1.

2. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: In step 1), the dilute acid is dilute hydrochloric acid or dilute sulfuric acid.

3. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: Step 2) The concentration of FeSO4 solution in the electrolyte is 0.3-0.5 mol / L, and the concentration of lactic acid is 2-4 mol / L.

4. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: In step 3), the concentration of the cobalt nitrate solution is 1.4-2 mol / L, and the concentration of the hexamethylenetetramine solution is 0.08-0.12 mol / L.

5. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: In steps 2) and 3), the pH is adjusted by using ammonia water, sodium hydroxide or potassium hydroxide solution with a mass concentration of 25%.

6. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: In step 3), Ag / AgCl is used as a reference electrode, a platinum sheet is used as a counter electrode, and an iron mesh containing a FeO film is used as a working electrode.

7. The method for preparing the Cu / Mn co-doped CoO / FeO catalyst according to claim 1, characterized in that: In step 4), the concentration of the copper chloride solution is 0.1-0.3 mol / L, and the concentration of the manganese nitrate solution is 0.2-0.3 mol / L. 2+ and Mn 2+ The molar ratio is (2:1)-(1:1.3).

8. A catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The catalyst is Cu x Mn y @Co 1-x-y O / FeO, wherein 0<x<0.1, 0<y<0.

1.

9. Use of the catalyst as claimed in claim 8 in catalytic degradation of polychlorinated biphenyls in organic wastewater, characterized in that: The following steps are involved: a) The Mn / Cu ion co-doped CoO / FeO catalyst is placed in a quartz glass tube of a liquid film photoreactor, and the set temperature of the liquid film photoreactor is 20-30°C and the pressure is 0.1-0.3MPa; b) adding the organic wastewater to be treated into the quartz tube, placing the catalyst in the organic wastewater, sealing the quartz tube, and introducing argon into the liquid film photoreactor under dark conditions at a flow rate of 90-110 mL / min for 20-40 min, and exhausting the gas in the reactor; c) Under the irradiation of a xenon lamp with an irradiation power of 300-400W, after the reaction for 5-10 hours, the concentration of polychlorinated biphenyls before and after the reaction was measured.

Citation Information

Patent Citations

  • Cobalt cerium composite metal oxide, its preparation method and its application

    CN102407127A

  • MoS2-doped iron oxide photocatalytic thin film and preparation method as well as application thereof to treatment of phenolic waste water

    CN105597784A